Fifty-fifty : - Wilson, Warren (Longman Asia ELT, 2007)
Fifty - fifty is the three level course in communicative English that provides speaking and listening practice for students from the elementary level through the intermediate level. This book is suitable for students at the elementary level who may have some passive knowledge of grammar and vocabulary from previous study, but lack the skills and confidence to participate in conversation